Designing Knowledge‐In‐Use Assessments to Promote Deeper Learning. Issue 2 (4th April 2019) - Harris, Christopher J.; Krajcik, Joseph S.; Pellegrino, James W.; DeBarger, Angela Haydel
Abstract: Contemporary views on learning highlight that deep learning occurs not simply by accumulating knowledge, but by using and applying knowledge as one engages in disciplinary activity. Increasingly, those concerned with education policy and practice are shifting priorities toward supporting deeper learning by emphasizing the importance of students' ability to apply knowledge in subject areas. Designers of student assessments are following suit and are taking on the challenge of creating a new generation of assessments. We present a principled approach for designing classroom‐based assessments that not only assess deeper learning, but also provide teachers with critical information about how students are progressing toward achieving ambitious new learning goals. Our approach follows the evidentiary reasoning of evidence‐centered design and builds on research about the important role of knowledge‐in‐use to support student learning. We illustrate our approach in the context of creating tasks that assess students' science proficiency as reflected in the Next Generation Science Standards that are gaining prominence in the United States.